Your Money or Your Speech: The Children’s Internet Protection Act and the Congressional Assault on the First Amendment in Public Libraries - Steven D. Hinckley (Washington University Law Quarterly, 2002)
CIPA is, in fact, one of the most sweeping restrictions on constitutionally protected speech ever invoked by the United States government disingenuously presented as an uncontroversial funding decision. By mandating the use of technology that cannot effectively eliminate obscenity and child pornography without compromising a great deal of protected speech, and by attempting to achieve indirectly content restrictions that the courts have held Congress cannot accomplish through direct statutory proscriptions, CIPA offends the First Amendment as surely as any prior failed attempt by the legislature to restrict Internet speech.
Keywords: Federal aid; Libraries; Spending power (Constitutional law); Internet censorship; Child pornography; Internet pornography; Freedom of speech; Internet filtering software; Public libraries; Children' s Online Privacy Protection Act of 1998